Determining the risk of predator attacks around protected areas: the case of Bardia National Park, Nepal. Issue 5 (2nd September 2020) - Upadhyaya, Subodh K.; Musters, C.J.M.; Lamichhane, Babu Ram; De Snoo, Geert R.; Dhakal, Maheshwar; De Iongh, Hans H.
Abstract: In this study we determined the probability of predator attacks on livestock around Bardia National Park, Nepal. We conducted semi-structured interviews to explore the patterns and factors affecting livestock losses in four administrative sectors of the Park's buffer zone. We developed models to investigate the overall probability of livestock loss, economic damage caused, and the respondents' attitudes towards wildlife. The probability of leopard attacks on livestock was much higher (85% of all livestock lost to depredation) than that of tiger attacks (8%), and the northern sector experienced the highest loss of livestock (50% modelled probability of livestock loss) in the buffer zone. Livestock loss was significantly related to the number of livestock owned by respondents, their ethnic group, and village distance to the Park boundary. Economic damage was influenced by buffer zone sector, number of livestock owned, and distance to the Park boundary. Conservation attitudes depended on respondents' knowledge of wildlife, levels of education and self-sufficiency, and the probability of livestock being killed by leopards. Respondents who were male, highly educated and self-sufficient were most likely to support conservation. Tigers are tolerated based on religious beliefs, and these cultural values, together with the sharing of conservation benefits, facilitate conservation. Leopards, however, are not tolerated in the same way and are the most damaging predators.